Pengaruh Peregangan Senam Ergonomis terhadap Skor Nyeri Musculoskeletal Disorders (MSDs) pada Pekerja Pembuat Kaleng Alumunium - Fatsiwi Nunik (IJNP (Indonesian Journal of Nursing Practices), 2015)
The use of human labor to manually in industry often lead to complaints, particularly in parts of the skeletal muscle complaints. This complaint termed musculoskeletal disorders (MSDs). MSDs can trigger maladaptive response to the workers as lazy in doing his work, late for work, work absence, and the work that is not optimal. The main strategy to deal with complaints of MSDs is gymnastics ergonomic. The aims of this study was to determine the effect of ergonomic exercises to decrease pain musculoskeletal disorders (MSDs) in aluminum cans workers. This study used quasy experiment with pre-and post-test control group design, that was conducted in July and August 2014. The sample in this study was 30 people’s were divided into intervention group and control group with 15 people’s in each group. Instruments in this study was the Nordic Body Map Questionnaire. Statistical analysis used parametric test (T test dependent and T test independent) and non parametric (Wilcoxon dan Mann Whitney test).The results showed there is decrease MSDs pain score from 19 to 13 score in ntervention group after done gymnastics ergonomic with p0.05. Based on statistical test with p0.05 this showed that there are diff erences changes in pain scores MSDs between the intervention group and control group signifi cantly. The conclusion of the research there was gymnastic ergonomic intervention can reduce MSDs pain in aluminum cans workers. It is recommended for workers to perform gymnastic ergonomics exercises regularly at least 2x a weeks before and after work.Keywords: pain, musculoskeletal disorders, ergonomic gymnastics